Fluoxetine Ecofriendly Nanoemulsion Enhances Wound Healing in Diabetic Rats: In Vivo Efficacy Assessment - Nabil A. Alhakamy; Giuseppe Caruso; Anna Privitera; Osama A. A. Ahmed; Usama A. Fahmy; Shadab Md; Gamal A. Mohamed; Sabrin R. M. Ibrahim; Basma G. Eid; Ashraf B. Abdel-Naim; Filippo Caraci (MDPI AG, 2022)
Impaired diabetic wound healing is a major concern for health care professionals worldwide, imposing an intense financial burden and reducing the quality of life of patients. A dysregulation of this process can be responsible for the development of intractable ulcers and the formation of excessive scars. Therefore, the identification of novel pharmacological strategies able to promote wound healing and restore the mechanical integrity of injured tissue becomes essential. In the present study, fluoxetine ecofriendly nanoemulsion (FLX-EFNE) was prepared and its potential efficacy in enhancing wound healing was tested in diabetic rats. The Box-Behnken response surface design was used to select the optimized formulation that was prepared by the high-shear homogenization-based technique. A Zetasizer was used for the characterization of the optimized formulation, providing a FLX-EFNE with a globule size of 199 nm. For the in vivo study, a wound was induced by surgical methods, and diabetic rats (streptozotocin-induced) were divided into five groups: untreated control, vehicle-treated, FLX, FLX-EFNE, and positive control receiving a commercially available formula. The treatment continued from the day of wound induction to day 21. Then, the animals were sacrificed and skin tissues were collected at the site of wounding and used for biochemical, histopathological, immunohistochemical, and mRNA expression assessments. In the FLX-EFNE treated group, the rate of wound contraction and signs of healing were significantly higher compared to all other groups. In addition, angiogenesis, proliferation, and collagen deposition were enhanced, while oxidative stress and inflammation decreased. The present data highlight the enhanced wound healing activity of the optimized FLX-EFNE formulation.